Forest Climate Projects in Russia: Practical Issues of Land Use - Svetlana S. MORKOVINA; Denis K. KUZNETSOV; Vyacheslav A. OROBINSKIY (Communications of International Proceedings, 2024)
This article is devoted to the assessment of the potential of the land resources of the Russian Federation for the implementation of forest climate projects. In the course of the work, various sources of data on the state of lands in the Russian Federation were analyzed, types of forest climate projects and conditions under which land plots may be suitable for forest climate projects were considered. As a result of the conducted research, the land areas of the forest fund for the implementation of various types of forest climate projects have been established.
Keywords: climate changes; forest climate projects; forest economy; low-carbon development